2012
DOI: 10.3390/molecules17010716
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Immunity Activity of Glycyrrhizin in AR Mice

Abstract: In this study, we evaluated effect of glycyrrhizin on immunity function in allergic rhinitis (AR) mice. The AR mice model were induced by dripping ovalbumin in physiological saline (2 mg mL−1, 10 μL) into the bilateral nasal cavities using a micropipette. After the AR model was induced, mice were randomly divided into six groups: the normal control, model, lycopene 20 mg kg−1 (as positive control drug) group, and glycyrrhizin 10, 20, 30 mg kg−1 groups. After the sensitization day 14, lycopene (20 mg/kg BW) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 60 publications
2
24
0
1
Order By: Relevance
“…Many studies shown that GL attenuated inflammatory responses due to decreased activation of nuclear factor kB (NF-kB) and mitogen-activated protein kinase (MAPK) pathways [87], moreover, inhibited the production of LPSinduced nitric oxide (NO) and tumor necrosis factor-α (TNF-α), prostaglandin E2, intracellular reactive oxygen species (ROS), proinflammatory interleukins as IL-4, IL-5, IL-6, IL-18, IL-1β [88][89][90][91][92], and increased the production of anti-infiammatory interleukins as IL-12 and IL-10 [92].…”
Section: Definition Pharmacokinetics and Biological Aspectsmentioning
confidence: 99%
“…Many studies shown that GL attenuated inflammatory responses due to decreased activation of nuclear factor kB (NF-kB) and mitogen-activated protein kinase (MAPK) pathways [87], moreover, inhibited the production of LPSinduced nitric oxide (NO) and tumor necrosis factor-α (TNF-α), prostaglandin E2, intracellular reactive oxygen species (ROS), proinflammatory interleukins as IL-4, IL-5, IL-6, IL-18, IL-1β [88][89][90][91][92], and increased the production of anti-infiammatory interleukins as IL-12 and IL-10 [92].…”
Section: Definition Pharmacokinetics and Biological Aspectsmentioning
confidence: 99%
“…In previous study by Abe et al up-regulation of IL-10 secretion by liver DCs in mice treated with GL has been reported 38 . We in our previous study on murine splenic DCs, and Hua and colleagues in their study on DC2.4 cell line have shown a similar effect for GL in enhancing IL-10 production 29 . There are some evidences that during Th1 responses, these cells can secrete IL-10 that in a regulatory-feedback loop will limit Th1 responses 39 .…”
Section: Discussionmentioning
confidence: 79%
“…Recent studies suggest that GL is able to attenuate inflammatory responses mediated by Toll-like receptors (TLRs) 28 . GL treatment could reduce blood interleukin IL-4, IL-5, IL-6 and TNF-a levels and nitrous oxide synthase activity in allergic rhinitis mice 29 .…”
Section: Discussionmentioning
confidence: 99%
“…However, pinellic acid alone was not sufficient to induce all the anti-allergic activities of SCRT, and some other active constituents seem to play a combinatorial role in the medicine [15]. Other ingredients such as paeoniflorin [23], a-asarone [24], Schizan [15], drin [25], 6-gingerol [26] and glycyrrhizic acid [27,28] have also been suggested to contribute to a protection against allergy. The present study demonstrated that SCRT is effective to treat AR in a mouse model.…”
Section: Discussionmentioning
confidence: 92%